Bio-oils from vacuum ablative pyrolysis of torrefied tobacco residues. Issue 58 (22nd September 2020) - Khuenkaeo, Nattawut; MacQueen, Blake; Onsree, Thossaporn; Daiya, Sangu; Tippayawong, Nakorn; Lauterbach, Jochen
Abstract : Thermochemical conversion of tobacco residues to value-added bio-fuels and chemicals via fast pyrolysis, in combination with torrefaction pretreatment, in a rotating blade ablative reactor under vacuum conditions. Abstract : Fast pyrolysis, in combination with torrefaction pretreatment, was used to convert tobacco residues to value-added bio-fuels and chemicals. Tobacco plant residues were torrefied at 220, 260, and 300 °C, before being pyrolyzed at 450, 500, 550, and 600 °C in a rotating blade ablative reactor under vacuum conditions to test the effects on product yields. With torrefaction, tobacco residues thermally decomposed 20–25% w/w at low temperatures. Torrefaction and pyrolysis temperatures were found to markedly affect pyrolytic product yields of bio-chars and bio-oils, while having no effect on gas-phase products. Bio-oil yields exhibited a direct relation with pyrolysis temperature and an inverse relation with torrefaction temperature. Bio-oils produced were separated into light and heavy oils and analyzed by GC-MS, and 1 H and 13 C NMR. Nicotine was found to be the main compound in the light and heavy oils along with several phenols and cresols in the heavy oil.